البدعة و موقف السنة النبوية منها نبذة عن الرسال - Rahima Sikumbang (Tamaddun, 2017)
Maintaining the purity of the source of Islamic shari'ah from the irresponsible person is something urgent, and always done by salafusshalihin scholars since the time of the prophet. Bid.ah has existed in the time of the Prophet, and progressed in the days of companions, and the tabi'in until now. Islam, from the point of worship of its nature tauqifiyyah, (fixed and certain)), should be based on shari'ah which has been determined by AlQuran, Assunnah, Qiyas, and the agreement of scholars. If the worship done without shari'ah, it is pertained as bid'ah. In accordance with the hadith of the Prophet narrated in the book of Muslim Sahih Bukhari: "Whoever does things that not based on the religion,the worship is rejected" meanwhile, in human relationships, is permissible, there is no prohibition for that. In this case, the author tries to overcome the problems that arise among the Muslim community of Indonesia in general, and West Sumatra in particular. This issue includes the celebration of the Prophet's birth,, a legacy in Minangkabau, Tabuik, 10 days after death, 40 days after death, etc. The author tries to examine the law that is often a controversy by some scholars. There are those who proclaim not to blame a practice. The author in this case trying to find the right solution in terms of Assunnah Annabawiyyah, therefore the authors begin by explaining what is Bid'ah, the historical development of bid'ah, the examples of heretical among the Muslim community in general, indonesia in particular, the cause of bid’ah, and the solution